2003
DOI: 10.1292/jvms.65.865
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Sugar Cane Extracts (SCE) on Eimeria tenella Infection in Chickens

Abstract: ABSTRACT. The effects of oral administration of sugar cane extracts (SCE) on Eimeria tenella oocysts infection in chickens were studied with 2 different experiments. In Experiment 1, 3-week-old inbred chickens (MHC; H.B15) were inoculated into the crop with SCE (500 mg/kg/day) for 1 day or 3 consecutive days, and then challenged with E. tenella sporulated oocysts (2 × 10 4 cells/chicken). In Experiment 2, 1-week-old chickens were orally administered SCE at the same dose for 3 consecutive days, and then initial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 28 publications
2
30
0
Order By: Relevance
“…Alternatively, SCE has displayed a wide range of biological effects including immunostimulation (El-Abasy et al, 2002), antiinflammatory activity (Ledon et al, 2003), activity as a vaccine adjuvant (El-Abasy et al, 2003) and anti-stress effects (Brekhman et al, 1978). Studies on chickens indicate that SCE acts as an adjuvant and has a protective effect against Eimeria tenella infection (El- Abasy et al, 2003). Other effects of SCE including antibacterial activities and superoxide anion scavenging activity (Takara et al, 2002) have been reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, SCE has displayed a wide range of biological effects including immunostimulation (El-Abasy et al, 2002), antiinflammatory activity (Ledon et al, 2003), activity as a vaccine adjuvant (El-Abasy et al, 2003) and anti-stress effects (Brekhman et al, 1978). Studies on chickens indicate that SCE acts as an adjuvant and has a protective effect against Eimeria tenella infection (El- Abasy et al, 2003). Other effects of SCE including antibacterial activities and superoxide anion scavenging activity (Takara et al, 2002) have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that protuberant cells indicate hypertrophy. As SCE induced growth-promoting (El-Abasy et al, 2002) and immunostimulatory effects (El-Abasy et al, 2003) and the probiotics could inhibit adhesion of pathogens to the chicken intestinal wall (Jin et al, 1996) by binding to intestinal mucus (Bernet et al, 1994), the observed protuberant cells may indicate hypertrophy as a result of feeding SCE or SPB. This corresponds with the fact that the SCE + SPB group showed the most conspicuously rough surface on the duodenal villus apical surface and that duodenal cell mitosis numbers were the highest in the SCE + SPB group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the chicken model, a dose of SCE between 500 and 1,500 mg/kg of body weight produces adjuvant and phylactic effects against viral, bacterial, and protozoal infections [6][7][8]. Decreasing the dose of SCE may reduce the protective effect against infections.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have indicated SCE can enhance resistance to secondary bacterial infection [1,19]. Studies on chickens indicate that SCE has an adjuvant effect on the activation of antibody and cell-mediated immune responses and provides a protective effect against Eimeria tenella infection [6]. These results suggest that SCE may positively regulate host natural immunity against viral, bacterial, and protozoal infections, via effects on the levels of macrophages, neutrophils and natural killer (NK) cells.…”
mentioning
confidence: 88%